Navigating The Challenges of Health Information Systems in The Saudi Healthcare System - Mohammad Yahya Hadadi , Zainab Ahmed AlBashrawi , Mohammed Abdullah Algharib , Fahad Mohaimeed Alotaibi , Othman Ibrahim Alghamdi; Fatimah Ali Hassan Albaladi, Esra Shabeeb Mohammed Al Shabeeb, Meshari Mohammed Humays, Yahya Hassan Mussa Kamili, Norah Ayed Khalaf Alanzi, Rawhiyah Hamdan Moazzi Al-Anzi, Moneera Rashed Al dossary, Abdulaziz Awad Zahian Alotaibi (Journal of International Crisis and Risk Communication Research, 2024)
The adoption of Electronic Medical Records (EMR) systems in Saudi Arabia is a critical component of the nation's Vision 2030 healthcare transformation agenda. Despite significant progress in digitizing healthcare delivery, the implementation of EMR systems faces multifaceted challenges. This comprehensive literature review explores the technical, financial, human, cultural, and policy-related barriers, as well as privacy and security concerns, that impede the successful adoption of EMR in the Saudi healthcare context. The review also highlights the systemic challenges surrounding medical coding, including workforce readiness, technological infrastructure, and regulatory coherence. Success stories and case studies offer valuable insights into effective EMR deployment strategies, emphasizing strong leadership, user engagement, vendor support, and culturally attuned implementation approaches. Emerging trends, such as the integration of artificial intelligence, telemedicine, and blockchain technologies, present promising opportunities to enhance EMR functionality and trust. To realize the full potential of EMR systems, a holistic and coordinated approach is necessary, aligning technological innovation with human factors, policy reform, and cultural sensitivity. By addressing the identified barriers and building on current research, Saudi Arabia can achieve a digitally empowered healthcare system that delivers efficient, equitable, and patient-centered care in line with its national vision.